Efectos de vinazas sobre bacterias rizosféricas y en la actividad-co2 y biomasa-c microbiana de un suelo pachic haplustoll (2013)
The effect of the application of vinasse, a byproduct of the fuel alcohol industry on growth promoting rhizosphere bacteria (Pseudomonas fluorescens and Bacillus subtilis), in Activity-CO2 and microbial biomass -C and metabolic quotient-qCO2 a Pachic Haplustoll, and its relationship to the performance of bean (Phaseolus vulgaris L.). We used a completely randomized design with seven treatments and five repetitions. The treatments were designed based on the requirements of the crop K+ (150 kg ha-1 K2O, Vallejo and Estrada 2004) and made up for using KCl and vinasse combined. The results show significant differences in activity and microbial biomass in the second and third sampling respectively. The highest values of microbial activity are presented in T5 and T7 minors; Microbial biomass presented the highest values in T3 and T7 minors. Rhizosphere bacteria differ significantly; Pseudomonas fluorescens in the second sampling, showing the highest values T5 and T6 minors. Bacillus subtilis differs in the third sample and the highest values reported in T4 and T1 minor. The negative correlation between metabolic ratio and yield beans, in this way, higher dry matter values are shown in the T6 and T5 minor